AN ELECTROPHORETIC STUDY OF THE HAEMOGLOBINS OF FISH FROM HUSSAINSAGAR LAKE - CHITRA, K. Y.; RAMKUMAR, N. SREE (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
The effect of water pollution on the electrophoretic pattern of haemoglobin from Channa punctatus and Tilapia mossambica of Hussainsagar lake was studied. The electrophoretic analysis revealed three district components in Channa punctatus and two in case of Tilapia. Both control and polluted water fish displayed the same electrophoretic pattern. However, the intensities of the bands were more in the polluted water fishes when compared to those in the respective control fishes.